Clinical features of pulmonary arterial hypertension in patients receiving dasatinib. Issue 11 (12th October 2015) - Shah, Neil P.; Wallis, Nicola; Farber, Harrison W.; Mauro, Michael J.; Wolf, Robert A.; Mattei, Daniele; Guha, Mausumee; Rea, Delphine; Peacock, Andrew
<x xml:space="preserve">Abstract</x> The prognosis of most leukemia patients treated with BCR‐ABL tyrosine kinase inhibitors (TKIs) is favorable, and a more precise understanding of serious and potentially irreversible treatment‐related toxicities is essential to properly inform treatment choice. Few cases of pulmonary arterial hypertension (PAH) have been reported in patients with leukemia treated with dasatinib, a second‐generation BCR‐ABL TKI. To better understand characteristics and outcomes of dasatinib‐treated patients with PAH, all clinical cases of PAH confirmed by right‐heart catheterization in the Bristol‐Myers Squibb pharmacovigilance database (N = 41), including 22 previously unpublished cases, were examined for previous treatments for leukemia, patient characteristics, time to PAH onset, and outcomes. Our analysis shows that compared with PAH due to other etiologies, dasatinib‐related PAH is atypical, in that it is associated with partial to complete reversibility upon treatment discontinuation. The incidence of dasatinib‐related PAH appears to be low. Most PAH cases were observed in patients who had received prior treatments for leukemia. No specific patient attributes appear to be associated with an increased risk of developing PAH while receiving dasatinib. Symptoms of PAH in dasatinib‐treated leukemia patients should prompt a thorough workup, including consideration of confirmatory right‐heart catheterization. In cases of confirmed PAH, dasatinib should be discontinued. Am. J. Hematol. 90:1060–1064, 2015. © 2015 Wiley Periodicals, Inc.